Ivermectin resistance mechanisms in ectoparasites: a scoping review - Furnival-Adams, J; Kiuru, C; Sagna, AB; Mouline, K; Maia, M; Chaccour, C (Springer, 2024)
Ivermectin mass drug administration has been used for decades to target human and veterinary ectoparasites, and is currently being considered for use against malaria vectors. Although there have been few reports of resistance to date in human ectoparasites, we must anticipate the development of resistance in mosquitoes in the future. Hence, through this review, we mapped the existing evidence on ivermectin resistance mechanisms in human ectoparasites. A search was conducted on the 8th November 2023 through databases, PubMed, Web of Science, and Google Scholar, using terms related to ivermectin, human and veterinary ectoparasites, and resistance. Abstracts (5893) were screened by JFA and CK. Data on the study organism, the type of resistance, the analysis methods, and, where applicable, the gene loci of interest were extracted from the studies. Details of the methodology and results of each study were summarised narratively and in a table. Eighteen studies were identified describing ivermectin resistance in ectoparasites. Two studies described target site resistance; and 16 studies reported metabolic resistance and/or changes in efflux pump expression. The studies investigated genetic mutations in resistant organisms, detoxification, and efflux pump expression in resistant versus susceptible organisms, and the effect of synergists on mortality or detoxification enzyme/efflux pump transcription. To date, very few studies have been conducted examining the mechanisms of ivermectin resistance in ectoparasites, with only two on Anopheles spp. Of the existing studies, most examined detoxification and efflux pump gene expression, and only two studies in lice investigated target-site resistance. Further research in this field should be encouraged, to allow for close monitoring in ivermectin MDA programmes, and the development of resistance mitigation strategies. Graphical Abstract: